2010
DOI: 10.5539/mas.v4n3p46
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Model of Traffic Volume Based on Grey-Markov

Abstract: Grey-markov forecasting model of traffic volume was founded by applying the model of GM (1,1) and Markov random process theory. The model utilizes the advantages of Grey-markov GM (1,1) forecasting model and Markov random process in order to discover the developing and varying tendency of the forecasting data sequences of traffic volume. The analysis of an example indicates that the grey-markov model has good forecasting accuracy and excellent applicability in predicting traffic volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…Specifically in transportation, the applications of the theory mainly have been on volume, traffic accident, and pavement design. Among them, GM(1,1) is combined with a Markov transition matrix by (Zhang (2010)) to forecast annual average daily traffic data. A comparison study by ) presents performance of GM(1,1) against back propagation neural network (NN) and radial basis function NN.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in transportation, the applications of the theory mainly have been on volume, traffic accident, and pavement design. Among them, GM(1,1) is combined with a Markov transition matrix by (Zhang (2010)) to forecast annual average daily traffic data. A comparison study by ) presents performance of GM(1,1) against back propagation neural network (NN) and radial basis function NN.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above analysis, we know that the model GM (1,1) and the Markov model could be integrated with each other to forecast by their advantages. That is: model GM (1,1) can be used to forecast the change trend of data sequences, while the Markov chain model can be used to decide the vibration regulation of their development [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Markov state transition matrices play the remedial role in overcoming the limitation of the grey forecasting model and are discussed in recent works. These literatures in [46][47][48] indicated that Markov state matrices have clearly increased the accuracy of grey forecasting models.…”
Section: Grey Markov Model (Mgm)mentioning
confidence: 99%